Improving VIII Grade Students’ Mathematical Problem Solving Ability Through Realistic Mathematics Education - I Made Ari Purwadi (Southeast Asian Mathematics Education Journal, 2020)
This paper aims to describe the improvement of students'  mathematical problem solving (MPS)  ability on the topic of simultaneous linear equations systems through  Realistic Mathematics  Education  (RME).  Nineteen students of  VIII  grade in  SMP  Laboratorium Undiksha in the first semester of the academic year 2019/2020 participated as the research subject.  This classroom action research consists of three cycles and every cycle contains three meetings. The data was collected by observation and essay-test before being analyzed using descriptive statistics. The finding is that the average score of the students’ MPS ability increased from 71,92 in the first cycle, to 73,2 in the second cycle, and to 75 in the third cycle. As demonstrated, the implementation of RME could increase students’ MPSability.  Hence,  the implementation of  RME has made students more motivated,  more active during the discussion and learning process,  solve problems more easily,   and communicate their understanding better.